Synthesis, Crystal Structure and Spectra Properties of Cd(II) Complex with 1,5-Diamino-3-oxapentane - Li, Congfen; Bai, Yuchen; Shi, Furong; Yang, Zaihui; Wang, Cuiping; Wu, Huilu (Asian Journal of Chemistry, 2014)
A new complex of the cadmium(II) nitrate with 1,5-diamino-3-oxapentane (L), with the composition is [Cd(L)(NO3)2], was synthesized and characterized by elemental analyses and IR spectra. The crystal structure of the complex has been determined by the single-crystal X-ray diffraction. The molecular structure consists of a ligand L, two nitrate radical and a Cd (II) atom. In the complex, the Cd(II) atom is N, O, N'-chelated by a ligand L and is further coordinated by two nitrate anions in a distorted monocapped octahedral geometry. The crystal structure is mainly stabilized by the intermolecular hydrogen bond.